2001
DOI: 10.1097/00004424-200107000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Glucose Alters the Susceptibility of Mesangial Cells to Contrast Media

Abstract: These findings suggest that high-glucose conditions enhance the susceptibility of MCs to the cytotoxic effects of both contrast media; the enhanced susceptibility was in part attributable to oxidative stress caused by high-glucose conditions; diatrizoate exerted the cytotoxic effects by means of oxidative stress; and iohexol appeared to exert its cytotoxicity in a manner different from diatrizoate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 33 publications
2
19
0
Order By: Relevance
“…Given all that, ERK1/2 and JNK expression might be involved in iodinated contrast media-induced renal cell apoptosis in diabetic rats. Based on the findings of our study and others, 11,12,[15][16][17][26][27][28][29] we propose a pathophysiologic mechanism for apoptosis induced by ionic HOCM in diabetic rats (Figure 4). According to these findings, ERK1/2 and JNK pathway may be a target for novel therapeutic intervention in CIAKI.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Given all that, ERK1/2 and JNK expression might be involved in iodinated contrast media-induced renal cell apoptosis in diabetic rats. Based on the findings of our study and others, 11,12,[15][16][17][26][27][28][29] we propose a pathophysiologic mechanism for apoptosis induced by ionic HOCM in diabetic rats (Figure 4). According to these findings, ERK1/2 and JNK pathway may be a target for novel therapeutic intervention in CIAKI.…”
Section: Discussionsupporting
confidence: 75%
“…Therefore, the hyperglycemia itself makes the kidney more susceptible to CIAKI. 22 Several in vitro studies also 11,12 demonstrated that high-glucose condition enhanced the susceptibility of renal cells to the cytotoxic effects (apoptosis) of both the HOCM and LOCM. In other words, the combination of high-glucose and contrast media has a synergistic effect on accentuating renal tubular apoptosis and therefore increasing the risk of CIAKI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(D) (C) studies, 21,22 and also on the fact that ICM are concentrated in the kidneys compared with blood plasma. Urinary concentrations of ICM can be up to 50-100 times that in plasma.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies suggest the generation of ROS as an important mechanism of direct RAs cytotoxicities. [7,8] The recommended clinical procedure used to reduce RA-induced damage to the kidneys is hydrating the patient before the administration of the RAs. [9][10][11][12] Recently, N-acetyl-cysteine, an antioxidant agent, has been used for RAs nephrotoxicities preventions.…”
Section: Introductionmentioning
confidence: 99%